Graphene Array-Based Anti-fouling Solar Vapour Gap Membrane Distillation with High Energy Efficiency - Gong, Biyao; Yang, Huachao; Wu, Shenghao; Xiong, Guoping; Yan, Jianhua; Cen, Kefa; Bo, Zheng; Ostrikov, Kostya (Nano-micro letters, 2019)
Highlights New concept of solar vapour gap membrane distillation (SVGMD) is based on synergizing of nanochannel-guided water transport, localized heating, and membrane separation from feed solution. First-time introduction of the gap enables long-term stability and non-fouling membrane. SVGMD exhibits a solar-water energy efficiency higher than state-of-the-art solar vapour systems. Photothermal membrane distillation (MD) is a promising technology for desalination and water purification. However, solar-thermal conversion suffers from low energy efficiency (a typical solar-water efficiency of ~ 50%), while complex modifications are needed to reduce membrane fouling. Here, we demonstrate a new concept of solar vapour gap membrane distillation (SVGMD) synergistically combining self-guided water transport, localized heating, and separation of membrane from feed solution. A free-standing, multifunctional light absorber based on graphene array is custom-designed to locally heat the thin water layer transporting through graphene nanochannels. The as-generated vapour passes through a gap and condenses, while salt/contaminants are rejected before reaching the membrane. The high solar-water efficiency (73.4% at 1 sun), clean water collection ratio (82.3%), excellent anti-fouling performance, and stable permeate flux in continuous operation over 72 h are simultaneously achieved. Meanwhile, SVGMD inherits the advantage of MD in microorganism removal and water collection, enabling the solar-water efficiency 3.5 times higher compared to state-of-the-art solar vapour systems. A scaled system to treat oil/seawater mixtures under natural sunlight is developed with a purified water yield of 92.8 kg m −2 day −1 . Our results can be applied for diverse mixed-phase feeds, leading to the next-generation solar-driven MD technology.